Internal Structure Evaluation on the Indonesian Version of Psychological Well-Being Scales - Darmawan Muttaqin (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2022)
The purpose of this research is to examine the internal structure of the Indonesian version of the Psychological Well-Being Scales (PWBS). This is a quantitative and cross-sectional research with the convenience sampling method used to obtain data from 1,337 students. The validity of the PWBS internal structure is evaluated using confirmatory factor analysis, exploratory structural equation modeling (ESEM), and composite reliability. The results showed that the Indonesian version of the 42-item PWBS and the 18-item PWBS do not have a satisfactory factor structure and internal consistency. Instead, it has few items that can accurately measure the concept of psychological well-being and are less able to represent the concept proposed by Ryff (1989). However, this research is not the only evidence that the Indonesian version of the PWBS cannot be used to measure psychological well-being.